Learners’ Perceptions of Writing Difficulties on a Pre-sessional EAP Programme in a British University - McCray, Diana; Hanks , Judith (Journal of Academic Writing, 2023)
This study examines how learners’ perceptions of their academic writing difficulties changed over the course of a four-week intensive English for Academic purposes (EAP) programme at a British university. The participants of this qualitative study were 14 Chinese undergraduate students who engaged in interviews and completed learning journal entries. The results of the thematic analyses indicate that vocabulary which constituted the biggest perceived challenge in Week 1 was no longer mentioned in Week 4 as a source of writing difficulty. Another finding is that after four weeks, students felt they had a better understanding of argumentation in a UK academic context and were not facing major difficulties with using sources and the understanding of argumentation in a UK academic context; they also reported that they were not facing major difficulties with using sources and understanding plagiarism in written assignments. Upon completion of the EAP course, students also reported that they tended to experience noticeably fewer challenges with academic reading. This qualitative study provides insights into the contribution of pre-sessional programmes in the development of learners’ writing as they transition into the academic community.